Adherence with Antiretroviral (ARV) Treatment of People with HIV (ODHIV) at Teladan Medan Health Center - Sarah Fadhila Siregar; Donal Nababan; Janno Sinaga; Daniel Ginting; Asima Sirait (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Indonesia is the 5th most at-risk country for HIV/AIDS in Asia. HIV/AIDS cases have become a problem in the world and are the 4th leading cause of death. In overcoming the issue of HIV/AIDS, patients must take antiretroviral drugs which only improve the quality of life. However, in reality, there are still many sufferers who are not compliant with the treatment being carried out. This study aims to analyze the factors that influence compliance with ARV treatment at the Teladan Medan Health Center. This study uses a quantitative research type with a descriptive approach. The study was conducted on PLHIV at the Teladan Medan Health Center starting from September 2023 - March 2024. The study population was 1,356 people, and the sample was taken from 150 people using a purposive sampling technique. The instruments used were adopted from previous studies that had been tested for validity and reliability and for the saturation variable using the medication saturation questionnaire by the Maslach Burnout Inventory. The results of the study showed that the majority of knowledge of PLHIV at Teladan Medan Health Center was in the good category as many as 121 (80.7%), the distance of PLHIV health services to the Health Center was mostly far as many as 90 (60%), the majority of PLHIV had experienced side effects as many as 111 (74%), the majority of PLHIV had experienced stigma as many as 89 (59.3%), boredom as many as 98 (65.3%) and the majority of PLHIV did not receive support in ARV treatment as many as 114 (76%). It can be concluded that the factors that influence adherence to ARV treatment are knowledge, distance of service, side effects of drugs, stigma, boredom and family support. Keywords: Antiretroviral, Human Immunodeficiency Virus , Compliance